2008
DOI: 10.1111/j.1745-4603.2007.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Sponge‐dough Bread Using Scalded Rye

Abstract: In this work, flatbed scanning, instrumental texture analysis, spectrophotometric color determination (L*, a*, b*), moisture and specific volume measurements were used to evaluate the effects of the addition of rye flour or rye flakes, yeast and boiling water in different amounts in sponge‐dough rye bread production. The treatments changed significantly (P < 0.05) the crumb cell area (mm2), cell diameter (mm), cell perimeter (mm), texture parameters and light reflectance (L*, a*, b*). Scalding process could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…However, there is not yet a standardized technique for this evaluation as differences among the reported IA methodologies for acquiring images by scanning or when pre-processing or processing these images to obtain crumb features are found. Some of these differences among the reported methodologies are about the scanning resolution, where it is possible to find reports using 150 dpi (Skendi et al 2010;Crowley et al 2000), 200 dpi (Esteller and Lannes 2008;Esteller et al 2006;Collar et al 2005), 300 dpi (Pérez-Nieto et al 2010;Lagrain et al 2006Lagrain et al , 2008, 350 dpi (Rosell and Santos 2010;Gonzales-Barron and Butler 2006), 550 dpi (López-Guel et al 2010), 600 dpi (Baiano et al 2009) or even without reporting the scanning resolution applied to the analysis. In the same context, the range of cells used to evaluate the crumb features, with some exceptions (Pérez-Nieto et al 2010;Skendi et al 2010;Gonzales-Barron and Butler 2008b;Crowley et al 2000) is not mentioned.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, there is not yet a standardized technique for this evaluation as differences among the reported IA methodologies for acquiring images by scanning or when pre-processing or processing these images to obtain crumb features are found. Some of these differences among the reported methodologies are about the scanning resolution, where it is possible to find reports using 150 dpi (Skendi et al 2010;Crowley et al 2000), 200 dpi (Esteller and Lannes 2008;Esteller et al 2006;Collar et al 2005), 300 dpi (Pérez-Nieto et al 2010;Lagrain et al 2006Lagrain et al , 2008, 350 dpi (Rosell and Santos 2010;Gonzales-Barron and Butler 2006), 550 dpi (López-Guel et al 2010), 600 dpi (Baiano et al 2009) or even without reporting the scanning resolution applied to the analysis. In the same context, the range of cells used to evaluate the crumb features, with some exceptions (Pérez-Nieto et al 2010;Skendi et al 2010;Gonzales-Barron and Butler 2008b;Crowley et al 2000) is not mentioned.…”
Section: Introductionmentioning
confidence: 90%
“…In recent years, image analysis (IA) has been used as quantitative tool for the assessment of crumb features (Zayas 1993;Sapirstein et al 1994;Crowley et al 2000;Riva and Liviero 2000;Lagrain et al 2006;Gonzales-Barron and Butler 2006;Calderón-Domínguez et al 2008;Ribotta et al 2010) and digital scanners to capture bread crumb two dimensions (2D) high-resolution images (Esteller and Lannes 2008;Datta et al 2007;Lassoued et al 2007;Esteller et al 2006). Hatcher et al (2004) reported that the use of a scanner for image acquisition, for the assessment of oriental noodle appearance and colour, offers all the advantages of previously investigated camera based systems, while Esteller et al (2006) explained that the acquisition of 2D images by flatbed scanning is fast, easy to use, economical, robust, independent of the external light conditions and with good accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical characteristics (moisture, pH, reducing sugars, and microstructure) of the dough are determinants of color characteristics (Esteller and Lannes, 2008). The left panel in Fig.…”
Section: Color Analysis Of Bread Variationsmentioning
confidence: 99%
“…Color depends on the physiochemical characteristics of the dough and also processing of the bread. Chemical reactions can affect the color of baked products, including browning reactions such as the Maillard reaction, which is affected by the moisture content, temperature, and pH (Esteller and Lannes 2008).…”
Section: Colormentioning
confidence: 99%